2020
DOI: 10.1158/1055-9965.epi-19-1363
|View full text |Cite
|
Sign up to set email alerts
|

Fine Particulate Matter Air Pollution and Mortality among Pediatric, Adolescent, and Young Adult Cancer Patients

Abstract: ◥Background: Air pollution is a carcinogen and causes pulmonary and cardiac complications. We examined the association of fine particulate matter pollution (PM 2.5 ) and mortality from cancer and all causes among pediatric, adolescent, and young adult (AYA) patients with cancer in Utah, a state with considerable variation in PM 2.5 .Methods: We followed 2,444 pediatric (diagnosed ages 0-14) and 13,459 AYA (diagnosed ages 15-39) patients diagnosed in 1986-2015 from diagnosis to 5 and 10 years postdiagnosis, dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 79 publications
(93 reference statements)
0
22
0
Order By: Relevance
“…140 Finally, a Utah study reported significant adverse PM 2.5 cancer mortality associations among pediatric patients with lymphoma and CNS tumors as well as among adolescent and young adult patients with CNS tumors, carcinomas, melanomas, breast cancers, and colorectal cancers. 141 Further research of mortality among patients with childhood cancer is needed.…”
Section: Epidemiological Studies Of Outdoor Air Pollution and Childhood Cancermentioning
confidence: 99%
“…140 Finally, a Utah study reported significant adverse PM 2.5 cancer mortality associations among pediatric patients with lymphoma and CNS tumors as well as among adolescent and young adult patients with CNS tumors, carcinomas, melanomas, breast cancers, and colorectal cancers. 141 Further research of mortality among patients with childhood cancer is needed.…”
Section: Epidemiological Studies Of Outdoor Air Pollution and Childhood Cancermentioning
confidence: 99%
“… PM 2.5 Mexico 2007 - 2011 509 mothers Increased the risk of Postpartum depression and neuropsychological dysfunction in mothers Niedzwiecki et al (2020) 10. PM 2.5 Utah 1986 - 2015 2,444 pediatric patients and 13,459 young adult patients with cancer Increases cancer mortality in pediatric lymphomas and CNS tumors Ou et al (2020a) 11. PM 2.5 Barcelona 2012 - 2014 186 participants Decreased corpus callosum volume in pre-adolescent children and behavior problems Mortamais et al (2019) 12.…”
Section: Impact Of Pm On the Nervous Systemmentioning
confidence: 99%
“…The risk for respiratory events was significantly higher among childhood cancer survivors than population comparisons without a cancer history (OR 1.84, 95% CI: 1.13-3.00 per 10 µg/m 3 ) [48]. PM 2.5 exposure from diagnosis through 5 and 10 years after diagnosis was also associated with all cause and cancer mortality among pediatric, adolescent, and young adult survivors (AYA) with certain diagnoses [49].…”
Section: Cancermentioning
confidence: 97%